Dinosaur origins: evidence from the footprint record - Marsicano, Claudia Alicia (2007)
Triassic tracks and trackways assigned to dinosaur trackmakers or closest relatives have been mentioned from several Middle to the latest Triassic successions from both northern and southern Pangea. At present, the earliest gondwanan records are those from the Middle Triassic Los Rastros Formation in west-central Argentina. A reanalysis of Los Rastros ichnites at the Ischichuca area, including new material, has revealed the presence of a more diverse ichnofauna than previously suspected. The ichnocoenosis includes several tracks and trackways of bipeds with functionally tridactyl digitigrade pes, well developed claws, and a parasagittal posture of the hindlimbs. Previously, some large tridactyl footprints from the Ischichuca area were allied to theropod dinosaurs, although no synapomophies are preserved in the three-toed footprints that might discriminate among theropods, basal saurischians and basal ornithischian groups as their possible trackmakers. If the Ischichuca trackmakers are referred to a dinosaur taxon and/or to a close dinosaur sister-taxon, their presence in the Los Rastros levels suggests that derived dinosauriforms (including dinosaurs) had diverged and acquired their characteristic functionally tridactyl pes by at least the Middle Triassic, something that the body-fossil record has failed to document to date.